The Characteristic of Heat Pump Dehumidifier Drier in the Drying of Red Chili (Capsium annum L) - Tjukup Marnoto; Endang Sulistyowati; Mahreni Mahreni; M. Syahri (International Journal of Science and Engineering, 2012)
Preservation of agricultural products have a very important to avoid the dropped of selling price when the harvest season arrives. Agricultural products are perishable because of high water content approximately 80 % which if the moisture content above 10% encourages proliferation of spoilage microorganisms in the material and cause the short shelf life. One way that has been done to preserve agricultural products such as red chili is dried using direct sunlight. Weakness of the sun drying can not reduce the water content to below 10% so spoilage microorganisms can live and breed, cause the short self life. Drying using Heat Pump Humidification Technology (HPD) is one solution to overcome the disadvantages of the direct sun drying. HPD can reduce the moisture content up to or below 10% will increase the self life and make easier to crush and to produce a chili powder. The purpose of this study to determine the appropriate mathematical model of the drying phenomena. The constant of the model equations are determined by Sum Square Error (SSE). Before being dried chilies dipped in hot water to remove the wax. PHD is used as an air dehumidifier that circulate in the dryer. Humidity difference causes the displacement of water from the chilies to dry air and lower the moisture content of chili. Moisture content of chili every 5 minutes is analyzed using gravimetric method. The results showed that the texture of the chili is very fragile with a moisture content of less than 10% and in the best conditions, the moisture content of chili is 6:35 wt%. From the research found that the appropriate model is Lewis model and the constant of the models obtained (k = 0.0056). Due to the moisture content of the product below 10 wt%, PHD can be considered as an agricultural product dryer. Keywords — Chili, drying, heat pump, hpd